Atomic nitrogen density measurements by actinometry method in the toroidal device NAGDIS-T. (30th July 2020) - Kajita, Shin; Asaoka, Koji; Tanaka, Hirohiko; Nishio, Ryosuke; Tsutsumi, Takayoshi; Hori, Masaru; Ohno, Noriyasu
Abstract: Nitrogen (N) atomic density is measured by an actinometry method in the toroidal shaped plasma device NAGDIS-T, where the plasma produced in a DC arc discharge is cooled as spiraling down inside the vacuum vessel. The plasma was characterized with an electrostatic probe, and we applied the actinometry method to obtain the N density using the deduced electron density and temperature. The actinometry method used the Ar line emissions at 750.4 or 811.5 nm and N emission at 746.8 nm. The measured N densities from the actinometry was compared with that from the vacuum ultraviolet absorption spectroscopy.